PURIFICATION OF DUG WELL WATER FROM Escherichia coli BY USING CARBON OF RICE HUSK - Hagar Karlani; Fahrul Fahrul; Maria M Meiwati; Herianus Manimoy; Loth Botahala (UIN AR-RANIRY, 2020)
Clean water is one of the human's main needs. Dug well water in Tombang, used for various needs. However, the dug well water has been polluted by E. Coli bacteria which is suspected to be due to the disposal of rubbish and waste carelessly and also the distance of latrines and dug wells that are very close together. Therefore it is important to do water purification using agricultural waste that is not utilized. The analysis showed that the purification of dug well water in Tombang with rice husk charcoal had reduced E. Coli bacteria by 55.6% with MPN pattern 1-0-3 so that the MPN value was 11/100 mL of sample.